2009
DOI: 10.1038/bmt.2009.209
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family education in HSCT: improving awareness of respiratory virus infection and influenza vaccination. A descriptive study and brief intervention

Abstract: To prevent respiratory virus (RV) infection after hematopoietic SCT (HSCT), patient and household members are advised to have annual influenza vaccinations and avoid symptomatic contacts. The object of this study was to measure and increase patient/household awareness of RV infection and preventive measures. We used a selfadministered questionnaire before/after a 5-min educational module (2006)(2007) and interviews with HSCT patients (2005with HSCT patients ( -2007. The subjects were patients and their house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…The importance of knowledge, skills, and attitudes in educating individuals to change behavior has been described in the CF community 381,382 as well as for healthcare personnel. [383][384][385][386][387] Knowledge, or facts, can be taught using didactic or case-based methods at the bedside or in the clinic. Adults learn best if they perceive the relevance of the information to their personal situation and are provided with the rationale.…”
Section: Ivb Education Strategiesmentioning
confidence: 99%
“…The importance of knowledge, skills, and attitudes in educating individuals to change behavior has been described in the CF community 381,382 as well as for healthcare personnel. [383][384][385][386][387] Knowledge, or facts, can be taught using didactic or case-based methods at the bedside or in the clinic. Adults learn best if they perceive the relevance of the information to their personal situation and are provided with the rationale.…”
Section: Ivb Education Strategiesmentioning
confidence: 99%
“…All were involved in consultations, were encouraged to attend education days, and received printed information, and each chose to engage with or ignore these educational measures according to their individual preferences. In fact, according to one evaluation, only 57 percent of patients attended the information day sessions (Ferguson, Jordens, and Gilroy 2010). These patients said nothing in their interviews that would indicate they were aware that the health care professionals treating them had strong expectations that the patients had a responsibility to engage with these educational measures, however.…”
Section: There Was One Young Girl Who Kind Of Pulled the Blankets Umentioning
confidence: 99%
“…Patients also are provided with electronic and printed materials (e.g., Bone Marrow Transplant Network NSW 2006) and are invited to attend information sessions at the hospital that combine formal presentations by members of the transplant team and transplant survivors, with informal opportunities to talk to the presenters. These information sessions are formally evaluated and are described elsewhere (Ferguson, Jordens, and Gilroy 2010).…”
Section: Expectations Placed On Physiciansmentioning
confidence: 99%
“…An adjuvanted 2009 pandemic influenza A/H1N1 vaccine was less immunogenic in SOT recipients than healthy controls [42]. Influenza vaccination of health care providers [43] and household contacts [44] of transplant candidate and recipients is imperative to create a "circle of protection" around this vulnerable population. A recent study showed that influenza vaccination of children and adolescents with inactivated influenza vaccine significantly protected even unimmunized residents of rural communities [45].…”
Section: Tx-vac-no Flu (N=13)mentioning
confidence: 99%